Experimental Investigation of Flood Energy Dissipation through Embankment Followed by Emergent Vegetation - Ahmed, Afzal; Valyrakis, Manousos; Razzaq Ghumman, Abdul; Pasha, Ghufran Ahmed; Farooq, Rashid (Periodica Polytechnica Civil Engineering, 2021)
The combination of hard (artificial) and soft (natural) solutions i.e., composite defense systems against flooding and tsunami opens a new window for engineering innovation for researchers nowadays. In this study, the experimental investigation of flood energy dissipation phenomena through composite defense systems comprising of embankment and rigid vegetation models in an open channel flume, is conducted. The flow regime through the composite defense system is classified in two main types, which are further subdivided in two sub-categories. Various combinations of embankment and vegetation and spacing between embankment and vegetation are analyzed. Against the selected range of initial Froude numbers, three different sizes of embankment models, three spacings between the embankment and vegetation (Ldv) and vegetated corridors of two different porosities (PR), are tested to examine the effect of these three parameters on the characteristics of the generated hydraulic jumps and flood energy dissipation within the defense system. It is found that embankment size and vegetation porosity have a greater impact on flood energy dissipation while the selected range of Ldv is less effective. Amongst the assessed composite flood defense systems, the maximum energy dissipation (55%) is observed for the combination of maximum embankment height and vegetation porosity (93%). For fixed combinations of embankment size and Ldv, the maximum increase of energy dissipation (18%) is found for decreasing vegetation porosity from 97% to 93%.